2013
DOI: 10.1016/j.jaut.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric disease in murine lupus is dependent on the TWEAK/Fn14 pathway

Abstract: Given the early onset of neuropsychiatric disease and the potential response to immunosuppressive therapy, neuropsychiatric disease is considered a primary disease manifestation in SLE. However, the pathogenesis is not fully understood and optimal treatment has yet to be determined. TWEAK is a TNF family ligand that mediates pleotropic effects through its receptor Fn14, including the stimulation of inflammatory cytokines by astrocytes, endothelial cells, and other non-hematopeotic cell types, and induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 51 publications
6
104
0
Order By: Relevance
“…All values were Ig deposition was reduced and noticeable improvement in renal damage was observed. In a previous study, we showed no significant differences in autoantibody titers between these strains up to 22 weeks of age 38 ; here, we confirm and further extend this observation up until 38 weeks of age. Both anti-double-stranded DNA and antichromatin antibodies are closely associated with nephritogenicity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All values were Ig deposition was reduced and noticeable improvement in renal damage was observed. In a previous study, we showed no significant differences in autoantibody titers between these strains up to 22 weeks of age 38 ; here, we confirm and further extend this observation up until 38 weeks of age. Both anti-double-stranded DNA and antichromatin antibodies are closely associated with nephritogenicity.…”
Section: Discussionsupporting
confidence: 91%
“…2,40 Antibodies against ribosomal P (P0, P1, and P2) were measured using a commercially available kit from Aesku Diagnostics (Wendelsheim, Germany). 38 Sera were diluted to 1:100, and OD values were normalized to the average absorbance of sera from two sick control MRL/lpr mice.…”
Section: Determination Of Serum Antibody Concentrationsmentioning
confidence: 99%
“…This observation also confirms, in the MRL-lpr model, the robustness of emotional dysfunction by providing further evidence that such behavioral outcomes are likely a primary manifestation of autoimmunity rather than arising from nonspecific illness or peripheral organ pathology. Finally, MRLlpr mice also display anhedonia, another manifestation of murine depressive-like behavior [91], which is is a lack of response to pleasure or reward and is assessed experimentally in following the loss of the typical preference to drink sweetened fluids [92]. Anhedonia is classically considered as a hallmark diagnostic symptom of depression and, in this report, it correlates significantly with a depression-like phenotype in the forced-swim test.…”
Section: The Mrl-lpr Mouse Modelmentioning
confidence: 75%
“…Gene expression was analysed using Taqman assays (Life Technologies): Ccl2 (Mm00441242_m1) and Nphs1 (Mm01176615_g1). The values were normalised to GAPDH and RPL27 [8].…”
Section: Quantitative Real Time Pcrmentioning
confidence: 99%